The Effect of the Missouri Mathematics Project Learning Model on the Tenth Grade Student’s Mathematical Literacy Ability in Gender Perspective - Rahma, Mulyanti; Usman, Usman; Ahsan, Muhammad (Universitas Islam Negeri Sunan Kudus, 2022)
The students’ low ability on mathematical literacy caused by teachers’ monotonous learning process and lack of students’ participation in teaching and learning process. This research aims to determine if Missouri Mathematics Project (MMP) is able to improve students’ mathematical literacy ability more effectively than direct learning model. In addition, the researcher explores how gender affects the effectiveness of MMP. The gender contribution here is what the differences of male and female students’ mathematical literacy ability are. The approach used in this research is quantitative research and the method is quasi-experimental having design of non-equivalent controlled group design. There are 70 students of grade X as sample consisting 35 students in experimental classes and 35 students in controlled classes (simple random sampling technique). The data taken in this research through mathematical literacy written test as the instrument and documentation. The analysis technique used is a two-way analysis of variance. The research results shows that students who are taught using the MMP model have significant effect on mathematical literacy ability than the students who are taught using direct learning. Female students’ mathematical literacy ability is better than the male students’ ability. There is a correlation between learning model and gender differences on mathematical literacy ability. Both male and female students’ mathematical literacy ability who are taught using MMP learning model is higher than male and female students’ ability who are taught using direct learning model Thus, MMP can be implemented as an alternative learning model to develop students' mathematical literacy ability. Kurangnya kemampuan literasi matematis dikarenakan oleh proses pembelajaran yang lebih monoton pada guru serta minimnya keaktifan siswa dalam proses pembelajaran. Studi ini untuk mengetahui apakah MMP (Missouri Mathematics Project) lebih efektif dalam mengembangkan literasi matematis daripada pembelajaran langsung. Selain itu, akan diekplorasi bagaimana gender mempengaruhi efektifitas MMP. Kontribusi gender yang dimaksud yaitu bagaimana perbedaan kemampuan literasi matematis antara laki-laki dan perempuan. Metode penelitian yang digunakan adalah kuantitatif dengan desain quaisy experimental. Sebanyak 70 siswa kelas X yang dijadikan sebagai sampel yang terdiri dari 35 kelas eksperimen dan 35 kelas kontrol (teknik simple random sampling). Instrumen penelitian dilakukan melalui tes literasi matematis, dan dokumentasi. Teknik analisis data menggunakan analisis varians dua jalur. Penelitian tersebut menemukan bahwa siswa yang diajar dengan model pembelajaran MMP memiliki literasi matematis lebih baik dibandingkan siswa yang diajarkan menggunakan pembelajaran langsung. Kemampuan literasi matematis siswa perempuan lebih tinggi daripada laki-laki. Terdapat interaksi antara MMP dengan perbedaan gender terhadap kemampuan literasi matematis. Kemampuan literasi matematis siswa laki-laki yang menerapkan MMP lebih tinggi dibandingkan dengan yang menerapkan pembelajaran langsung. Kemampuan literasi matematika siswa perempuan dengan menerapkan MMP lebih tinggi dibandingkan kemampuan siswa yang menerapkan pembelajaran langsung. Sehingga, MMP dapat dijadikan alternatif model pembelajaran untuk mengembangkan kemampuan literasi matematis siswa.